Carbon Emission Disclosure Evidence from Listed Companies in Indonesia: How Green Culture Moderate Leverage and The Green Strategy - Ratnasari, Martdian (Indonesian Journal of Sustainability Accounting and Management, 2026)
This study examines the influence of green strategy and leverage on carbon emission disclosure, as well as the moderating role of green culture in strengthening this influence. Data were analyzed using linear regression modeling. This model tests the direct and indirect effects of green strategy and leverage on carbon emission disclosure, and explores the interaction effect of green culture. The results show that the green strategy has a significant positive effect on carbon emission disclosure, and the green strategy is proven to be an important strategy indicator in increasing corporate transparency regarding environmental impacts. Furthermore, the influence of green strategy is strengthened by the existence of a strong green culture, which reflects an organization's internal commitment to environmental issues across the company's operations. In contrast, leverage and its interaction with green culture do not significantly affect the variability of carbon emission disclosure, suggesting that financial pressure from debt does not encourage more transparent corporate environmental reporting behavior. This study provides practical implications for stakeholders; investors are encouraged to consider green strategy and green culture when assessing a company's long-term impact on the environment. This study offers a more comprehensive theoretical contribution: green strategy, as a corporate strategic choice, is proven to be a key determinant of carbon disclosure compared to financial pressures such as high leverage. These results demonstrate the company's strategic commitment to environmental issues. Future research is recommended to use a longer observation period, add other financial and non-financial variables, and explore the long-term financial impact of environmental initiatives.